2014
DOI: 10.1002/aenm.201301413
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Recombination Through the Use of a Non‐Fullerene Acceptor in a 6.4% Efficient Organic Planar Heterojunction Solar Cell

Abstract: An optimization of several aspects of planar heterojunction solar cells based on boron subnaphthalocyanine chloride (SubNc) as a donor material is presented. The use of hexachlorinated boron subphthalocyanine chloride (Cl6SubPc) as an alternative acceptor to C60 allows for the simultaneous increase of the short‐circuit current, fill factor, and open‐circuit voltage compared to cells with fullerene acceptors. This is due to the complementary absorption of Cl6SubPc versus SubNc, reduced recombination at the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
80
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 38 publications
1
80
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In general, BsubPcs hold significant promise as organic electronic materials, 18 having been demonstrate as both electron donors, 19 electron acceptors, [20][21] and ambipolar interlayers 22 in singlet fission free organic photovoltaic devices. BsubPcs have been used with the complimentary absorbers α-sexithophene and subnaphthalcyanine chloride (Cl-BsubNc) to construct a planar heterojunction photovoltaic cell that absorbed a broad portion of the visible spectrum that also featured an energy cascade (transferring excitons from Cl-BsubPc to ClBsubNc within the cell) leading to a power conversion efficiency of up to ~8 %.…”
mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 In general, BsubPcs hold significant promise as organic electronic materials, 18 having been demonstrate as both electron donors, 19 electron acceptors, [20][21] and ambipolar interlayers 22 in singlet fission free organic photovoltaic devices. BsubPcs have been used with the complimentary absorbers α-sexithophene and subnaphthalcyanine chloride (Cl-BsubNc) to construct a planar heterojunction photovoltaic cell that absorbed a broad portion of the visible spectrum that also featured an energy cascade (transferring excitons from Cl-BsubPc to ClBsubNc within the cell) leading to a power conversion efficiency of up to ~8 %.…”
mentioning
confidence: 99%
“…[5][6][7] Additional research focus lies on the development of alternatives to fullerene-derivative acceptors which are commonly used but provide limited absorption. [ 8,9 ] Cnops et al recently reported highly effi cient fullerene-free organic cascade devices employing the vacuum-deposited organic materials α-6T, SubPc, and SubNc as active layers. [ 10 ] Even though the layer sequence is simple using neither doped nor coevaporated layers, a maximum effi ciency of 8.4% has been achieved.…”
Section: Doi: 101002/aenm201502432mentioning
confidence: 99%
“…Here, the limit to V OC has been ascribed to the HOMO-LUMO offset of the outermost semiconducting layers in the device stack [13] or alternately to the lowest value of DE DA at each interface [14]. Previous observations of V OC in cascade structures have found that adding an additional layer to a bi-layer cell, resulting in an energy loss step, does not reduce V OC appreciably [4,14]. However, others have observed the opposite [2,15] or mixed results [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…One promising material system consists of organic semiconducting small molecules and/or polymers, although limitations inherent to their excitonic nature, such as low open-circuit voltage (V OC ) and poor coverage of the solar spectrum, must be overcome [1]. New device architectures employing multiple molecular species in a cascade energy alignment have begun to address these limitations, demonstrating impressive gains in efficiency by employing two donor materials [2,3], exciton blocking layers [4], interstitial layers at the donor-acceptor heterojunction [5e8], or directed energy transfer [9,10].…”
Section: Introductionmentioning
confidence: 99%